2014
DOI: 10.1101/gr.162131.113
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations found in the healthy blood compartment of a 115-yr-old woman demonstrate oligoclonal hematopoiesis

Abstract: The somatic mutation burden in healthy white blood cells (WBCs) is not well known. Based on deep whole-genome sequencing, we estimate that approximately 450 somatic mutations accumulated in the nonrepetitive genome within the healthy blood compartment of a 115-yr-old woman. The detected mutations appear to have been harmless passenger mutations: They were enriched in noncoding, AT-rich regions that are not evolutionarily conserved, and they were depleted for genomic elements where mutations might have favorabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 51 publications
10
110
1
3
Order By: Relevance
“…However, these aberrations may not always be causative in the development of a primary tumor. This is reminiscent of our results and those of others showing that clonal cell expansions in normal blood are common and do not always lead to development of a clinical phenotype in subjects carrying such clones (Forsberg et al 2012(Forsberg et al , 2013(Forsberg et al , 2014Jacobs et al 2012;Laurie et al 2012;Holstege et al 2014;Score et al 2015). Furthermore, as shown in multiple figures, the aberrations detected in both UMs and PTs were present in PT samples in a considerably higher percentage of cells and were often accompanied by many additional aberrations that were present in PTs only.…”
Section: Propagation Of Genetic Aberrations From Ums Into Ptssupporting
confidence: 69%
“…However, these aberrations may not always be causative in the development of a primary tumor. This is reminiscent of our results and those of others showing that clonal cell expansions in normal blood are common and do not always lead to development of a clinical phenotype in subjects carrying such clones (Forsberg et al 2012(Forsberg et al , 2013(Forsberg et al , 2014Jacobs et al 2012;Laurie et al 2012;Holstege et al 2014;Score et al 2015). Furthermore, as shown in multiple figures, the aberrations detected in both UMs and PTs were present in PT samples in a considerably higher percentage of cells and were often accompanied by many additional aberrations that were present in PTs only.…”
Section: Propagation Of Genetic Aberrations From Ums Into Ptssupporting
confidence: 69%
“…The lessthan-perfect relationship in the longitudinal study of oldest-olds also suggests that methylation age is advancing at a slower rate than chronological age. In principle, it is possible that this phenomenon is related to an evolution of hematopoietic oligoclonality at extreme ages, which was recently suggested (Holstege et al, 2014), where the peripheral blood cells in long-living individuals are derived mainly from clones with a younger DNAm age.…”
Section: Discussionmentioning
confidence: 99%
“…Holstege et al 25 studied WGS of a 115-year-old woman with extreme CH and found no CD mutations (nor indeed any mutations present in the COSMIC catalog). This suggested that CH might occur in the absence of detectable CD mutations.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similarly, Holstege et al used this method to detect extreme CH without CD mutations in a 115-yearold woman. 25 We have sequenced the whole genomes of a substantial number of Icelanders. 26 Here we use the whole-genome sequence (WGS) data to search for CH events by counting the number of low-VAF mutations present in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%